Mass Diffusion of Modern Digital Technologies as the Main Driver of Change in Sports-Spectating Audiences - Glebova, Ekaterina; Desbordes, Michel; Geczi, Gabor (Frontiers in Psychology, 2022)
The rapid uptake of digital technologies is constantly transforming the modern culture of sports spectating; however, relatively little is known about the impact of digitalization on the changing face of global sports-consuming audiences, particularly from a qualitative perspective. In this article, the relationship between modern mass digital technologies (i.e., mobile applications and big data) and audiences of sports spectators is described and explained by taking a customer-centric approach to grounded theory using a literature review and in-depth qualitative semi-structured interviews (N = 12) with sports marketing, management, and technology professionals. The qualitative approach permits the gathering of in-depth insights into a problem, generates new concepts through data synthesis and analysis, and captures changing attitudes within the sports industry. Moreover, the qualitative approach to research is not bound by the limitations of quantitative methods and focuses on the primary questions of “how” and “why” digital technology’s mass deployment and diffusion have transformed content consumption in the sports industry. The analysis first systematizes and codes the collected data. Second, all the materials are iteratively read and the key points are outlined. Using the iterative analysis, the theoretical and empirical insights and findings are synthesized in order to achieve the results. Finally, dimensions of the transformation of sports spectators’ consumption are identified and explained. The research implications highlight “how” and “why” modern digital technologies have changed the sports-consuming audience by making it more inclusive in terms of age, gender, demographics, social and health status. These findings are useful for sport managers to better understand their audiences and processes in an ever-changing global society.